Pengembangan Snack Bar Berbasis Bahan Freeze-Dried Tape Ketan Hitam, Tepung Mocaf dan Tepung Kacang Almond sebagai Selingan untuk Diabetes Melitus - Edmon Edmon; Roro Nur Fauziyah; Agus Sulaiman; Witri Priawantiputri; Nur Ahmad Habibi (Poltekkes Kemenkes Padang, 2025)
The incidence of Diabetes Mellitus (DM) continues to increase globally and has become a serious health threat, including in Indonesia. Modern lifestyles, unbalanced diets, and genetic factors are the main causes. This study aimed to determine the best formulation of a Snack Bar made from freeze-dried black glutinous rice tape flour, mocaf flour, and almond flour, and to evaluate its organoleptic properties (color, aroma, taste, texture), anthocyanin content, antioxidant activity, and fiber content as an alternative solution for individuals with Type 2 DM. The study was conducted experimentally using a Completely Randomized Design (CRD) at Poltekkes Kemenkes Padang. Three formulations were tested organoleptically by panelists and analyzed in the laboratory for nutritional content. The results showed that the best formulation was F3 (20g black glutinous rice tape, 60g mocaf, 20g almond) with 84% panelist acceptance. Proximate analysis showed ash content of 1.18%, moisture 35.9%, protein 10.5%, fat 12.05%, carbohydrates 40.26%, fiber 2.15%, and anthocyanin 0.3 mg. It is concluded that the Snack Bar made from black glutinous rice tape, mocaf, and almond has potential as a functional food for people with DM. Further research is recommended to assess storage stability and conduct clinical trials for its effectiveness in controlling blood sugar levels.